POPULATION ESTIMATE OF FACTORS, FORMING THE HEALTH OF THE CHILDREN FROM THE FAR NORTH - S.A. Tokarev; A.A. Buganov ("Paediatrician" Publishers LLC, 2007)
The article gives a population estimate of the social and biological hazards of noncinfective diseases among children, living under extreme conditions of the far north. The authors show the high spread level of the most indicated factors. The researchers have identified almost all the factors of the nonc infective risk among the children cnortherners, who were born as a result of the pathologically run pregnancy. It is supposed to use the obtained data during the development and realization of the complex study and sanitary programs for the children, living in the regions of the far north.Key words: hazards, children of the far north, population estimate.